2004
DOI: 10.1016/s1097-2765(04)00210-2
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Sharp Bending of Double-Stranded DNA

Abstract: Sharply bent DNA is essential for gene regulation in prokaryotes and is a major feature of eukaryotic nucleosomes and viruses. The explanation normally given for these phenomena is that specific proteins sharply bend DNA by application of large forces, while the DNA follows despite its intrinsic inflexibility. Here we show that DNAs that are 94 bp in length-comparable to sharply looped DNAs in vivo-spontaneously bend into circles. Proteins can enhance the stability of such loops, but the loops occur spontaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

37
445
8
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 333 publications
(493 citation statements)
references
References 28 publications
37
445
8
3
Order By: Relevance
“…Difference free energies for wrapping of different 94 bp DNAs around the core histone H32H42 tetramer are plotted against the difference free energies of cyclization for these same DNAs. 74 The line illustrates the least-squares fit to the data. The slope of the line is one, implying that the entirety of the difference in affinity for wrapping around histones can be explained by the difference in the ability to cyclize.…”
Section: Figurementioning
confidence: 99%
“…Difference free energies for wrapping of different 94 bp DNAs around the core histone H32H42 tetramer are plotted against the difference free energies of cyclization for these same DNAs. 74 The line illustrates the least-squares fit to the data. The slope of the line is one, implying that the entirety of the difference in affinity for wrapping around histones can be explained by the difference in the ability to cyclize.…”
Section: Figurementioning
confidence: 99%
“…This form of the energy must break down for R sufficiently small, but this is not seen in the DNA stretching experiments where the highcurvature configurations are irrelevant [11]. In contrast, cyclization experiments initially suggested [12] that the high-curvature states of DNA are much more flexible than predicted by (1). There is some controversy about the exact range of validity of (1).…”
Section: Introductionmentioning
confidence: 96%
“…There is some controversy about the exact range of validity of (1). If we write this range of validity as R > Cl p =ð2 Þ, where C is a numerical factor (of order 1), then the initial suggestion from cyclization experiments [12] was C % 0:7, whereas Du et al argued that C is lower [13]; using DNA minicircles the study [14] found that C % 0:5. Other studies also reported softening of the DNA at small scales [15]; in particular, the Atomic Force Microscopy (AFM) study [11] reported that the measured correlation functions are best described by a linear (rather than quadratic) dependence of the energy on the bending angle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…100 bp),5 dsDNA bending has been a central debate in the field 4b. 6 Recently, a single‐molecule study showed extreme dsDNA bendability at less than 100 bp by analyzing real‐time cyclization kinetics 7.…”
mentioning
confidence: 99%